PERAN INSPEKTORAT DALAM MENINGKATKAN KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN PINRANG - Maulana, Eka (DECISION : Jurnal Ekonomi dan Bisnis, 2021)
The purpose of this study was to determine the role of the Pinrang Regency Inspectorate in improving the quality of the financial reports of the Pinrang Regency Government. This research uses descriptive qualitative research using a qualitative approach. Data were obtained from interviews, observations, and documentation. The results show that the Pinrang Regency Inspectorate has played an important role in improving the quality of the financial reports of the Pinrang Regency Government which for seven consecutive years received an Unqualified Opinion by increasing its work in terms of implementing performance audit supervision, auditing certain objectives, reviewing regional financial reports, monitoring, and evaluation of supervision as well as improvements in terms of coaching or consulting to audits and the Work Units of Service Equipment within the Pinrang Regency Government.